Comparison of Metaraminol, Phenylephrine, and Norepinephrine Infusion for Prevention of Hypotension During Combined Spinal-Epidural Anaesthesia for Elective Caesarean Section: A Three-Arm, Randomized, Double-Blind, Non-Inferiority Trial - Zhou Y; Yu Y; Chu M; Zhang Y; Yu X; Chen G (Dove Medical Press, 2022)
Youfa Zhou,1,* Yunyun Yu,1,2,* Miaofei Chu,1,3 Yanting Zhang,1 Xin Yu,1 Gang Chen1 1Department of Anesthesiology, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People's Republic of China; 2Department of Anesthesiology, Lishui Central Hospital, Lishui, Zhejiang, People's Republic of China; 3Department of Anesthesiology, Zhejiang Greentown Cardiovascular Hospital, Hangzhou, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Gang Chen Tel +8613757118681Fax +8657186044817Email chengang120@zju.edu.cnBackground: A direct comparison of phenylephrine, metaraminol, and norepinephrine in preventing hypotension during spinal anaesthesia for elective caesarean section has never been made.Patients and Methods: Seventy-five parturients scheduled for elective caesarean section were randomly assigned into the three groups. After spinal anaesthesia induction, patients received a bonus dose of vasopressor (norepinephrine 4ug, phenylephrine 50ug, or metaraminol 250ug) combined with continuous infusion (norepinephrine 8ug/mL, phenylephrine 100ug/mL, or metaraminol 500ug/mL) at a rate of 30 mL/h to prevent hypotension. The primary outcome was umbilical arterial (UA) pH and other intraoperative data were also recorded.Results: The UA pH was 7.32± 0.03 for metaraminol, 7.31± 0.03 for phenylephrine, and 7.31± 0.03 for norepinephrine. The 95% CI of MD was - 0.011 to 0.026 comparing metaraminol with norepinephrine and 0.0181 to 0.0182 comparing phenylephrine with norepinephrine. Both lower bounds of the 95% CI of MD were above the predetermined lower boundary of clinical non-inferiority of − 0.03, indicating both metaraminol and phenylephrine were non-inferior to norepinephrine. Moreover, the incidence of hypotension was lower in metaraminol compared with norepinephrine (P = 0.01). However, the incidence of hypertension was significantly lower in both phenylephrine and metaraminol compared with norepinephrine.Conclusion: Both metaraminol and phenylephrine were non-inferior to norepinephrine with respect to neonatal UA pH when used as a bolus and continuous infusion to prevent hypotension during combined spinal-epidural anaesthesia for elective caesarean section.Keywords: caesarean section, hypotension, metaraminol, phenylephrine, norepinephrine